A new X linked recessive syndrome of mental retardation and mild dysmorphism maps to Xq28. Issue 7 (July 1997) - Pai, G S; Hane, B; Joseph, M; Nelson, R; Hammond, L S; Arena, J F; Lubs, H A; Stevenson, R E; Schwartz, C E
Abstract : Efforts to understand the genetic basis of mental retardation are greatly assisted by the identification of families with multiple relatives with mental retardation that clinical geneticists encounter in the routine practice of their profession. Here we describe a linkage study of a four generation family in which X linked recessive mental retardation (XLMR) is associated with minor dysmorphism and premature death of the affected males. Microsatellite based polymorphic loci evenly spaced over the entire X chromosome were used initially to detect linkage to Xq28. Further analysis identified a haplotype of Xq28 markers bounded proximally by locus DXS1113 and distally by DXS1108 that cosegregated with XLMR in this family. Two point lod scores > 3.0 provided strong evidence that the gene locus responsible for XLMR in this family is within this 7 Mb region of Xq28. The minor anomalies noted in some affected males were not distinctive enough to suggest a unique syndrome. None of our patients had features of the Waisman-Laxova syndrome or the PPM-X syndrome. The possibility of allelism with any of the five other non-specific XLMR syndromes (MRX3, MRX16, MRX25, MRX28, and MRX41) mapped to Xq28 could not be excluded. While the recognition of a gene responsible for this disorder needs much additional work, multiple female relatives at risk in this family benefit immediately from knowing their genotype and heterozygotes will have the opportunity to undergo prenatal diagnosis.